(untitled) (Texas Journal of Philology, Culture and History, 2026)
This paper examines the understanding of the problem of time in the short stories of Anton Pavlovich Chekhov. It analyzes the features of the artistic representation of time, its connection with the inner state of the characters, and social changes in society at the end of the nineteenth century. Special attention is paid to how the writer reveals the transience of life, spiritual stagnation, and the conflict between the past, present, and future through everyday situations and the destinies of the characters. The study shows that the category of time in Chekhov’s works serves as an important means of revealing the psychological depth and philosophical richness of his prose